2010
DOI: 10.1111/j.1479-828x.2010.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal haemoglobin level at booking visit and its effect on adverse pregnancy outcome

Abstract: Although anaemia during pregnancy was not adversely associated with any of the pregnancy outcomes, Hb level of >13.9 g/dL was adversely associated with maternal morbidities and LBW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 16 publications
2
56
2
2
Order By: Relevance
“…This suggested that hemoglobin effects in developing countries ( n = 9 studies) [912, 16, 17, 28, 32, 34] were similar to the overall effects with the pooled ORs of 1.69 (95% CI: 1.28–2.23), 1.34 (95% CI: 1.17–1.53), 1.10 (95% CI: 1.02–1.19), and 0.93 (95% CI: 0.80–1.08) for hemoglobin cutoffs <9, <10, <11, and ≥14 g/dL, respectively. However, the hemoglobin effects were lower and nonsignificant in developed countries ( n = 2 studies) [18, 27] compared with developing countries with the pooled ORs of 1.17 (95% CI: 0.47–2.93) and 1.21 (95% CI: 0.59–2.51) for the cutoffs of <10 and <11 g/dL, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that hemoglobin effects in developing countries ( n = 9 studies) [912, 16, 17, 28, 32, 34] were similar to the overall effects with the pooled ORs of 1.69 (95% CI: 1.28–2.23), 1.34 (95% CI: 1.17–1.53), 1.10 (95% CI: 1.02–1.19), and 0.93 (95% CI: 0.80–1.08) for hemoglobin cutoffs <9, <10, <11, and ≥14 g/dL, respectively. However, the hemoglobin effects were lower and nonsignificant in developed countries ( n = 2 studies) [18, 27] compared with developing countries with the pooled ORs of 1.17 (95% CI: 0.47–2.93) and 1.21 (95% CI: 0.59–2.51) for the cutoffs of <10 and <11 g/dL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [912, 17, 27, 28, 31, 32, 34] assessed the association between low hemoglobin concentration in the first trimester and LBW with hemoglobin concentration ranging from 7 to 16 g/dL (Supplementary Table 3). Nine studies [912, 17, 28, 31, 32, 34] were conducted in developing countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sri Lanka, 5% -7% of the population have the Rh-Negative Blood group. This study also shows that 6.3% had Rh Negative blood group which is similar na- In Sri Lanka Syphilis (all forms of syphilis) constituted 10% of sexually transmitted infections in 2016 [15]. Overall 98.1% of pregnant mothers were tested for VDRL in Sri Lanka at the time of delivery.…”
Section: Discussionmentioning
confidence: 57%
“…37,38 Hence, whether the disordered maternal hemoglobin levels during pregnancy affect adverse birth outcomes is still in controversy. In healthy pregnant women, the lack of an increase in plasma volume during pregnancy is associated with lower birth weight and placental weight and an increased risk of delivering a small-for-gestational-age infant.…”
Section: Discussionmentioning
confidence: 99%